'A lot of people still love and worship the monarchy': How polarizing frames trigger countermobilization in Thailand. (January 2023) - Sombatpoonsiri, Janjira
This article examines the interplay between nonviolent movements' use of polarizing issues for mobilization and pro-regime countermobilization. Thailand has been chosen as an explanatory case study because it has a history of political polarization and pro-regime mass mobilization. I focus on polarizing frames that were incorporated into the 2020 nonviolent resistance campaigns, which addressed a taboo subject in the country: the monarchy. In response, the regime applied various forms of repression, including the mobilization of royalists. But the assumption that the regime single-handedly mobilized countermovements is only half of the story. Autonomous elements within countermovements also joined forces when there were sufficient social conditions. By juxtaposing protest event data with an analysis of mobilizing frames (through movements' Twitter hashtags), I shed light on a two-pronged process that underpins the nexus between framing choice and countermobilization: (a) how a movement's choice for polarizing frames sustains existing ideological and identity-based cleavages, antagonizing segments of society that perceive their collective identity to be under siege and; (b) how these ideological and identity-based cleavages also provide social sources for countermobilization. I conclude by addressing some implications of this framing choice–countermobilization nexus on repression dynamics and suggest how we can rethink the relationship between strategic framing and nonviolent resistance campaigns in divided societies.